ISLAMIC EDUCATION TOWARD THE ERA OF SOCIAL CHANGE: EFFORT IN ENHANCING THE QUALITY - Lubis, Saiful Akhyar (Journal of Al-Tamaddun, 2012)
The current social change demands Islamic education to be able to follow the flow of that change. Islamic education which considered by the majority as a "slow responds education in anticipating social changes" needs more professional management. Therefore, it is not only needed to preserve its existence, but also it needs consideration, future anticipation, and reorganization of all aspects. In behalf of making alternative solution, this article aims for observing within the problems of Islamic education in one aspect, and its relation to the social chance in another aspect. Finally, found the thing that must be realized frequently is send the meaning to education, and also its correlation with the future. It is also essential to think of how as a process it (education) shows its efficiency and able to produce output effectively